2004
DOI: 10.1163/22941932-90000370
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Auxin and Gibberellin in Gravity-Induced Tension Wood Formation in Aesculus Turbinata Seedlings

Abstract: The lowest nodes of 6-week-old Aesculus turbinata seedlings were treated with uniconazole-P, an inhibitor of gibberellin (GA) biosynthesis, or a mixture of uniconazole-P and GA3 in acetone solution. To the seedling stems, an inhibitor of auxin transport (NPA) or inhibitors of auxin action (raphanusanin or MBOA) were applied in lanolin paste. The seedlings were tilted at a 45° angle and kept for 10 weeks before histological analysis. Decreases in both normal and tension wood formation followed the application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
(31 reference statements)
3
19
0
Order By: Relevance
“…There was TW formation in trees treated with exogenous IAA (Figure 5b) and this observation is consistent with the report of Morey and Cronshaw (1968b). Du et al (2004) found that NPA inhibits TW formation if the cellular auxin transport is perturbed by NPA.…”
Section: Effects Of Iaa and Npasupporting
confidence: 91%
See 2 more Smart Citations
“…There was TW formation in trees treated with exogenous IAA (Figure 5b) and this observation is consistent with the report of Morey and Cronshaw (1968b). Du et al (2004) found that NPA inhibits TW formation if the cellular auxin transport is perturbed by NPA.…”
Section: Effects Of Iaa and Npasupporting
confidence: 91%
“…Different stimuli are known to induce TW formation, especially the gravitational and hormonal stimuli (Jin et al 2014;Gerttula et al 2015;Gritsch et al 2015;Roussel and Clair 2015). Auxins mediate seasonal changes of cambial activity as a positional signal (Uggla et al 1996(Uggla et al , 1998 and, probably, they also play a key role in the control of TW formation (Morey and Cronshaw 1968a;Du et al 2004). Auxins induced TW formation in Acer rubrum seedlings, especially at low concentrations (Morey and Cronshaw 1968b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many experimental studies have been carried out to describe the role of auxin in formation of reaction wood (Du et al, 2004;Funada et al, 1990;Phelps et al, 1977;Sundberg et al, 1994;Yamaguchi et al, 1980;Wardrop and Davies, 1964), involving a redistribution of auxin or auxin-transport inhibitors. These findings suggest that the formation of reaction wood is associated with a high level of auxin to induce compression wood (gymnosperms) and low level of auxin for tension wood (angiosperms).…”
Section: Introductionmentioning
confidence: 99%
“…The application of BA alone was not effective in promoting cambial activity and xylem formation until mixed with NAA. There have been reports regarding interactions between auxin and gibberellin and their role in plant growth (Ross et al 2000(Ross et al , 2002Ross and O'Neill 2001;Wolbang and Ross 2001) and on gravitropism and tension wood formation (Du et al 2004). Therefore, the control of negative gravitropism and tension wood formation by GA 3 and IAA in hardwood tree stems remains to be fully elucidated.…”
mentioning
confidence: 99%